Pengaruh Metode Multisensori Terhadap Kesulitan Membaca Siswa Kelas IV di Madrasah Ibtidaiyah Makassar - Wati, Srinur Indah; Mulyadi, Mulyadi; Alannasir, Wahyullah (ISOLEK: Jurnal Pendidikan, Pengajaran, Bahasa, dan Sastra, 2023)
Multisensory methods are used to learn to read and spell. The multisensory method uses a kinesthetic auditory visual approach (VAKT) to teach children reading difficulties to read. This research uses a quantitative research approach with a type of experiment. Research Design Experimental research was conducted using the One Group pre-test post-test experimental design. This design was carried out by forming a single experimental group that was given treatment. With the multisensory method, students will be given learning by utilizing visual memory (vision), auditory (hearing), kinesthetic (movement), and tactile (touch) abilities. The results of this study, namely the multisensory method, affect the reading difficulties of grade IV students of MI Makassar, it is based on a significance value of 0.001 where 0.000<0.05 then H0 is rejected and H1 is accepted. There is an average pre-test score of reading difficulties, which means there is an increase in the reading ability of grade IV MI Makassar City students